When the shoe fits : talks on the stories of Chuang Tzu - Osho, 1931-1990 (Rajneesh Foundation, 1976)
Discourses of a Hindu religious leader about the life and philosophy of the Chinese philosopher of the Taoist school, Chuang-tzu, d. c. 300 B.C.